Improved conversion efficiency of a‐Si:H/µc‐Si:H thin‐film solar cells by using annealed Al‐doped zinc oxide as front electrode material. (21st May 2013) - Neubert, Sebastian; Wimmer, Mark; Ruske, Florian; Calnan, Sonya; Gabriel, Onno; Stannowski, Bernd; Schlatmann, Rutger; Rech, Bernd
ABSTRACT In recent years, zinc oxide has been investigated as a front electrode material in hydrogenated amorphous silicon/hydrogenated microcrystalline silicon (a‐Si:H/µc‐Si:H) tandem solar cells. Such as for other transparent conducting oxide materials and applications, a proper balancing of transparency and conductivity is necessary. The latter is directly related to the density and the mobility of charge carriers. A high density of charge carriers increases conductivity but leads to a higher absorption of light in the near‐infrared part of the spectrum due to increased free‐carrier absorption. Hence, the only way to achieve high conductivity while keeping the transparency as high as possible relies on an increase of carrier mobility. The carrier density and the mobility of sputtered Al‐doped zinc oxide (ZnO:Al) can be tailored by a sequence of different annealing steps. In this work, we implemented such annealed ZnO:Al films as a front electrode in a‐Si:H/µc‐Si:H tandem solar cells and compared the results with those of reference cells grown on as‐deposited ZnO:Al. We observed an improvement of short‐circuit current density as well as open‐circuit voltage and fill factor. The gain in current density could be attributed to a reduction of both sub‐band‐gap absorption and free‐carrier absorption in the ZnO:Al. The higher open‐circuit voltage and fill factor are indicators of a better device quality of the silicon for cells grown on annealed ZnO:Al. Altogether, the annealing led to an improved initial conversion efficiency of 12.1%, which was a gain of +0.7% in absolute terms. Copyright © 2013 John Wiley & Sons, Ltd.